PENERAPAN WEBINAR DALAM UPAYA PENINGKATAN PENGETAHUAN TENTANG MANAJEMEN PASIEN DENGAN SINDROM KORONER AKUT - zayu, ade; Kamsiah; Fitria Anuril, Kheli; Nafratilova, Mercy; Susanto, Ari; Saferi Wijaya, Andra (Poltekkes Kemenkes Bengkulu, 2024)
Coronary heart disease is the number one killer and its incidence is increasing year by year. Acute Coronary Syndrome has a substantial association with morbidity and mortality and imposes a large financial burden on the healthcare system Diagnostic and therapeutic advances over the past few decades have significantly improved the health outcomes of patients with acute coronary syndrome. Acute coronary syndrome is a multifactorial disease, which is influenced by many factors, such as hypertension, DM and smoking habits. The purpose of this online seminar is to increase participants' knowledge about the definition, risk factors and management of acute coronary syndrome. The method used is to hold a webinar and evaluate knowledge about the management of patients with acute coronary syndrome. The webinar activity was held for 1 day with 4000 registrants. The webinar was attended by 1649 participants who filled in the attendance link. Participants who filled in the pretest link were 721 participants and posttest were 1297 participants. 657 participants filled in both links (Pretest and Posttest). From the results of the pretest and posttest knowledge evaluation, it shows that there is an increase in the average participant knowledge score at the pretest of 29.95%, increasing to 46.91% at the posttest, with Pvalue = 0.000. To increase knowledge can use webinars.